2022
DOI: 10.1021/acs.est.2c03076
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Water and Sanitation Challenges of Underbounded Communities in the U.S.

Abstract: Water and sanitation (wastewater) infrastructure in the United States is aging and deteriorating, with massive underinvestment over the past several decades. For many years, lack of attention to water and sanitation infrastructure has combined with racial segregation and discrimination to produce uneven access to water and wastewater services resulting in growing threats to human and environmental health. In many metropolitan areas in the U.S., those that often suffer disproportionately are residents of low-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Explanations of these observed siting-related disparities include selective migration of people of color into urban and industrial regions with more potential PFAS sources and demographic changes that preferentially increase the proportion of people of color after a source is developed in a community. Past studies have reported that environmental hazards are disproportionately sited near marginalized communities. , These communities may represent the “path of least resistance” due to limited political power, reduced access to information and resources, and restricted engagement in decision-making regarding siting. , Historical segregation has also shaped the spatial patterning of pollution sources around the U.S., and many areas remain highly segregated. Our analysis is consistent with preliminary reports suggesting that higher proportions of people of color live in proximity to sites potentially contaminated with PFAS…”
Section: Resultsmentioning
confidence: 99%
“…Explanations of these observed siting-related disparities include selective migration of people of color into urban and industrial regions with more potential PFAS sources and demographic changes that preferentially increase the proportion of people of color after a source is developed in a community. Past studies have reported that environmental hazards are disproportionately sited near marginalized communities. , These communities may represent the “path of least resistance” due to limited political power, reduced access to information and resources, and restricted engagement in decision-making regarding siting. , Historical segregation has also shaped the spatial patterning of pollution sources around the U.S., and many areas remain highly segregated. Our analysis is consistent with preliminary reports suggesting that higher proportions of people of color live in proximity to sites potentially contaminated with PFAS…”
Section: Resultsmentioning
confidence: 99%
“…Various types of AD technologies have been implemented widely in LICs and LMICs. Common household AD systems in LMIC include the fixed dome digester, the floating drum and the tubular or plug flow digester with the HomeBiogas system being a new addition to the market. , Although usually not considered AD technology, septic tanks are anaerobic treatment systems that are widely used in rural areas, unincorporated and underbounded urban environments, or households too far from centralized wastewater treatment systems to connect to sewers . In a septic tank, suspended solids in the influent waste stream settle to the bottom of the tank to allow for biodegradation.…”
Section: Anaerobic Digestion As a Sanitation Technology For Decentral...mentioning
confidence: 99%
“…Kalina et al identified the owner as the most important stakeholder and highlighted the owner’s ability and willingness to engage and understand AD technologies as a key indicator of project success. Involving community members through various phases of project planning and execution, considering their specific needs, and using local labor and materials, result in better uptake of the installed facilities and contribute to a sense of ownership. , Specific needs include not just the physical context of space and topography, but also the preferences, concerns, constraints, and capabilities of a community. Such demand-based, rather than supply-based systems, where communities commit to partnering have been noted as drivers for success in any sanitation project …”
Section: Implementation Partnerships and Engagement Of Stakeholders A...mentioning
confidence: 99%
“…In some U.S. communities, reliance on private wells is an environmental justice issue. Studies across the nation have documented communities of color that have been systematically excluded from access to municipal water infrastructure and therefore rely on private wells and/or septic systems, despite their close proximity to municipal water and sewer lines . Examples include Latino communities in California’s Central Valley and along the Texas/Mexico border and African American communities in Florida, North Carolina, and Ohio .…”
Section: Introductionmentioning
confidence: 99%